1975
DOI: 10.1093/infdis/132.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Cryptococcosis with a Combination of Flucytosine and Amphotericin B

Abstract: In a prospective study from May 1971 to November 1973, 20 consecutive patients with a diagnosis of disseminated cryptococcosis were treated for six weeks with a combination of amphotericin B (20 mg daily) intravenously and flucytosine (150 mg/kg daily) orally. Fifteen patients has culturally docummented Cryptococcus neoformans meningitis, and three died of infection early in therapy. Of the remaining 12 patients, eight were alive and well eight to 34 months after therapy, and four died of other causes. None of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0

Year Published

1976
1976
1981
1981

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(31 citation statements)
references
References 12 publications
2
29
0
Order By: Relevance
“…The great majority of patients develop disseminated disease, particularly involving the central nervous system. Many of these patients have had renal transplants, lymphoreticular malignancy, or immunosuppressive therapy (12,17,21,31). One common denominator of disseminated cryptococcosis has been the frequent association with an underlying deficit of cell-mediated immunity (CMI) (13,28).…”
mentioning
confidence: 99%
“…The great majority of patients develop disseminated disease, particularly involving the central nervous system. Many of these patients have had renal transplants, lymphoreticular malignancy, or immunosuppressive therapy (12,17,21,31). One common denominator of disseminated cryptococcosis has been the frequent association with an underlying deficit of cell-mediated immunity (CMI) (13,28).…”
mentioning
confidence: 99%
“…Several authors have suggested that bone marrow depression may be associated with the use of 5-fluorocytosine (5-FC) for the treatment of serious fungal infections (2,7,10,11,15). Leukopenia (2,15), thrombocytopenia (15), and pancytopenia (7,10,11) have been reported Although the toxic effect on the marrow ha:; been felt to be dose related, serum levels of 5-FC at the time of marrow depression have only infrequently been recorded (7).…”
mentioning
confidence: 99%
“…Although many patients have dramatically responded, the treatment is long, arduous, and complicated by both outright failures and late relapses after apparent responses (1,2). More recently the antimetabolite 5-fluorocytosine has been added in an effort to reduce the total dose (and toxicity) of amphotericin B (10). Although this has been largely achieved, 5-fluorocytosine has brought its own forms of gastrointestinal and hematological toxicity and therefore is not totally benign.…”
mentioning
confidence: 99%